Identifying Mutations of the Tetratricopeptide Repeat Domain 37 (TTC37) Gene in Infants With Intractable Diarrhea and a Comparison of Asian and Non-Asian Phenotype and Genotype: A Global Case-report Study of a Well-Defined Syndrome With Immunodeficiency. Issue 9 (March 2016) - Lee, Wen-I; Huang, Jing-Long; Chen, Chien-Chang; Lin, Ju-Li; Wu, Ren-Chin; Jaing, Tang-Her; Ou, Liang-Shiou
Abstract : Abstract: Syndromic diarrhea/tricho-hepato-enteric syndrome (SD/THE) is a rare, autosomal recessive and severe bowel disorder mainly caused by mutations in the tetratricopeptide repeat domain 37 (TTC37) gene which act as heterotetrameric cofactors to enhance aberrant mRNAs decay. The phenotype and immune profiles of SD/THE overlap those of primary immunodeficiency diseases (PIDs). Neonates with intractable diarrhea underwent immunologic assessments including immunoglobulin levels, lymphocyte subsets, lymphocyte proliferation, superoxide production, and IL-10 signaling function. Candidate genes for PIDs predisposing to inflammatory bowel disease were sequencing in this study. Two neonates, born to nonconsanguineous parents, suffered from intractable diarrhea, recurrent infections, and massive hematemesis from esopharyngeal varices due to liver cirrhosis or accompanying Trichorrhexis nodosa that developed with age and thus guided the diagnosis of SD/THE compatible to TTC37 mutations (homozygous DelK1155H, Fs*2; heterozygous Y1169Ter and InsA1143, Fs*3). Their immunologic evaluation showed normal mitogen-stimulated lymphocyte proliferation, superoxide production, and IL-10 signaling, but low IgG levels, undetectable antibody to hepatitis B surface antigen and decreased antigen-stimulated lymphocyte proliferation. A PubMed search for bi-allelic TTC37 mutations and phenotypes were recorded in 14 Asian and 12 non-Asian cases. They had similar presentations of infantile onset refractory diarrhea, facial dysmorphism, hair anomalies, low IgG, low birth weight, and consanguinity. A higher incidence of heart anomalies (8/14 vs 2/12; P  = 0.0344, Chi-square), nonsense mutations (19 in 28 alleles), and hot-spot mutations (W936Ter, 2779-2G>A, and Y1169Ter) were found in the Asian compared with the non-Asian patients. Despite immunoglobulin therapy in 20 of the patients, 4 died from liver cirrhosis and 1 died from sepsis. Patients of all ethnicities with SD/THE with the characteristic triad of T nodosa, hepatic cirrhosis, and intractable enteropathy have low IgG, poor vaccine response and/or decreased antigen-stimulated lymphocyte proliferation. This is now better classified into the subgroup of "well-defined syndromes with immunodeficiency" (the update termed as "combined immunodeficiencies with associated or syndromic features") than "predominantly antibody deficiencies" in the update PIDs classification, and requires optimal interventions. Abstract : Supplemental Digital Content is available in the text